EFFECT OF MOTOR VEHICLE TAX REALIZATION, NAME REVERSAL DUTY MOTOR VEHICLE AND SURFACE WATER TAXES AGAINST LOCAL REVENUE OF REMBANG REGENCY - Yulinar Puput Frastika; Riskin Hidayat (Jurnal Ekonomi, 2023)
This study aims to analyze the reliability of Motor Vehicle Tax, Vehicle Name Reverse Duty and Surface Water Tax on Local Original Revenue of Rembang Regency. The population in this study is the target data target and realization of regional income of Rembang Regency. The sampling technique in this study uses purposive sampling, which is a sampling technique with certain criteria. The data used in this study is secondary data, through target data and regional revenue realization for the 2017-2021 fiscal year of Rembang Regency, by accessing the BAPENDA website of Central Java Province http://pad-dppad.jatengprov.go.id:8080/jateng1/. The results showed thatPKB and BBNKB had a significant positive effect on the Regional Original Income (PAD) of Rembang Regency. Meanwhile, PAP has a negative insignificant effect on the Local Original Revenue (PAD) of Rembang Regency.